Risk and Crisis Management in the Public Sector - Drennan, Lynn T, 1953- (ROUTLEDGE MASTERS IN PUBLIC MANAGEMENT)
Every decision that is made by managers and policy-makers in a public sector organization requires an evaluation and a judgement of the risks involved. This vital requirement has been recognised in the growth of risk management. However, risks can nev